Meeting security challenges through data analytics and decision support - Shahbazian, E.; Rogova, Galina; Shabestari, Omid (NATO science for peace and security series, D, Information and communication security ;, 2016)
The aim of the conference was to promote and enhance cooperation and dialogue between NATO and Partner countries on the subject of effective decision support for security applications.